Double perovskite LiLaMgWO6:Eu3+ novel red-emitting phosphors for solid sate lighting: Synthesis, structure and photoluminescent properties. Issue 2 (1st February 2017) - Li, Li; Chang, Wenxuan; Chen, Wuyang; Feng, Zhongshan; Zhao, Chenglong; Jiang, Pengfei; Wang, Yongjie; Zhou, Xianju; Suchocki, Andrzej
Abstract: LiLaMgWO6 :Eu 3+ phosphors have been synthesized by high-temperature solid-state reaction and their structure, ultraviolet-visible diffuse reflectance spectra, photoluminescence and decay properties have been investigated as a function of the Eu 3+ concentration. The XRD results indicated that all the prepared phosphors can be assigned to a monoclinic double perovskite structure in space group C 2/ m . LiLaMgWO6 :Eu 3+ phosphor has exhibited excellent red emission and efficient excitation, consisting of a broad band ranging from 250 to 350 nm as well as several narrow excitation peaks between 450 and 580 nm. The presence of dominant red emission band centered at 615 nm suggested that Eu 3+ enters in the lattice site without inversion symmetry. The quenching concentration of Eu 3+ is up to 30 mol%. The theoretical quenching concentration and quenching mechanism were discussed herein. Moreover, the thermal quenching, CIE chromaticity coordinates, quantum yield, Judd-Ofelt analysis and energy transfer mechanism are discussed in detail.